PERCEPTIONS OF ORGANIZATIONAL LEARNING PRACTICES AMONG YEMENI UNIVERSITY LIBRARIANS - Abdullah, Khaled Ateik Saeed; Kassim, Norliya Ahmad (Malaysian Journal of Library and Information Science, 2008)
This study explores the perceptions of organizational level learning practices among university librarians in Yemen. The Dimensions of the Learning Organization Questionnaire (DLOQ) developed by Watkins and Marsick (1993) was used as the instrument for collecting data. Twenty-four variables were used to assess the perception of organizational level learning practices among senior and middle-level librarians of all Yemeni university libraries (seven public and 11 private). The response rate was 72% (n = 198). The results of the study show that the mean scores of learning practices at the organizational level were not enough to consider Yemeni university libraries as learning organizations. The result of comparison showed that the mean score rating for private university libraries is higher than the mean score for public university libraries. The study suggests the need for more studies of organizational learning in order to understand the barriers of practicing organizational learning. Furthermore, for effective organizational learning, the results propose institutionalizing individual and team learning as prerequisites.